Game Edukasi Interaktif Pembelajaran Tafsir Al-Qur’an Berbasis Mobile Menggunakan Metode MDLC - Hardiansyah, Nanda; Sarudin, Sarudin (Forum Kerjasama Pendidikan Tinggi, 2026)
The objective of this research is to develop an interactive mobile-based educational game that presents Qur’anic exegesis (tafsir) with an attractive and user-friendly interface. The game is designed to cover three surahs: Al-Ikhlash, Al-Falaq, and An-Nas. The content includes Arabic text, Latin transliteration, translation, and a concise tafsir summarized from Tafsir Ibn Kathir Volume I. The development method employed is MDLC (Multimedia Development Life Cycle), which offers clear and systematic stages, ranging from concept, design, material collection, production, testing, to distribution. This structured process facilitates project management, progress monitoring, interim evaluation, and effective integration of user or stakeholder feedback. A trial conducted with 30 elementary school students yielded positive results: the UI/UX aspect received 89.6% (YES) responses, while the game content aspect reached 89.7% (YES). These findings indicate that the design, usability, as well as tafsir and quiz content were perceived as engaging, easy to understand, and beneficial. The results demonstrate that the developed application can enhance students’ interest, understanding, and motivation in learning Qur’anic exegesis in an enjoyable, interactive way, while being relevant to current technological developments. Thus, this research provides a tangible contribution to the innovation of digital learning media beneficial for Islamic education.